Uniformity or Unilateralism in the Law of Carriage of Goods by Sea? - Myburgh, Paul (Victoria University of Wellington Law Review, 2000)
The ideal of international uniformity has always been regarded as particularly important to maritime law. However, over the past decade or so, the uniformity of the law of international carriage of goods by sea has increasingly been undermined by the unilateral adoption by maritime jurisdictions of "hybrid carriage regimes" which depart from the established international uniform rules. In this article Paul Myburgh argues that this trend towards adoption of divergent carriage regimes is highly problematic, not merely because of their detrimental effects on international uniformity and the coherence of maritime law and international transport law in general, but also because of more fundamental concerns about the validity of these regimes at international law, the practical conflict of laws problems that that they will generate, and their distorting effects on multimodal transport. The article concludes with some suggestions for future reform in this area.